2009
DOI: 10.1002/mmce.20408
|View full text |Cite
|
Sign up to set email alerts
|

Physical/electromagnetic analysis of multifinger MOSFETs with SB-SP combined methods

Abstract: The frequency-domain spectral balance technique has been demonstrated to be a viable alternative to the mixed-domain Harmonic Balance technique. It has already been applied to the space-domain polynomial expansion of the physical quantities inside the semiconductor, for the solution of steady-state nonlinear differential equations, for the physical analysis of high-frequency semiconductor devices. In this article it is coupled to a commercial electromagnetic solver, for the combined physical and electromagneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Electromagnetic (EM)-wave-shielding and/or absorbing materials have recently received increasing attention due to the rapid development of microwave applications in wireless communications, 1 high-frequency circuit devices, 2 and radar stealth systems. 3 Aside from conventional EM-wave-absorbing materials such as ferrites and carbonyl iron, nanomaterials such as SiC nanowires, 4 Fe/C nanotube cables, 5 Fe/C core-shell nanocapsules, 6 Ni/Ag coreshell nanoparticles, 7 Fe nanowires, 5 carbon fiber/carbonyl-iron, 8 and carbonyl-iron/rubber 9 have been recently studied. These studies found that nanomaterials have soft magnetic and dielectric characteristics, making them promising radar-absorbing materials (RAMs).…”
Section: Introductionmentioning
confidence: 99%
“…Electromagnetic (EM)-wave-shielding and/or absorbing materials have recently received increasing attention due to the rapid development of microwave applications in wireless communications, 1 high-frequency circuit devices, 2 and radar stealth systems. 3 Aside from conventional EM-wave-absorbing materials such as ferrites and carbonyl iron, nanomaterials such as SiC nanowires, 4 Fe/C nanotube cables, 5 Fe/C core-shell nanocapsules, 6 Ni/Ag coreshell nanoparticles, 7 Fe nanowires, 5 carbon fiber/carbonyl-iron, 8 and carbonyl-iron/rubber 9 have been recently studied. These studies found that nanomaterials have soft magnetic and dielectric characteristics, making them promising radar-absorbing materials (RAMs).…”
Section: Introductionmentioning
confidence: 99%